Effectiveness of Mathematical Learning Devices Based on Verbal Linguistic Intelligence and Mathematical Logical Intelligence - Tebe, Sry Rasyiidu; Anwar, Anwar; Bahrun, Bahrun (Universitas Malikussaleh, 2019)
2013 curriculum has mandated the importance of teachers and paying attention to aspects of diversity of students in learning, including intelligence. Based on the type of intelligence proposed by Gardner (2003), linguistic-verbal intelligence and mathematical logical intelligence are two intelligences that need to be considered by the teacher in mathematics learning, for example when the teacher prepares a mathematics learning tool. This study aimed to determine the effectiveness of mathematical learning tools based on linguistic-verbal intelligence and mathematical logical intelligence on material equations and linear inequalities. This study used the Plomp development model which consists of three phases, namely initial investigation, design, and assessment. The trial was carried out four times for students of class VII-8 in SMP Negeri 2 Banda Aceh. To determine the effectiveness of learning devices, criteria Kemp was applied, et al (1994). The results of the development showed that the mathematics learning tools based on linguistic-verbal intelligence and mathematical logical intelligence were effective. Because of that, this learning tool is worthy of being used by teachers in mathematics learning, especially in similarities material and linear inequalities.